DEFINITION OF ENERGY SAVING ACCELERATION MODES OF TRAINS - Bodnar, B. Ye.; Kapitsa, M. I.; Afanasov, A. M.; Kyslyi, D. N. (Science and Transport Progress, 2015)
Purpose. In modern conditions of rolling stock operation, the actual vital task is the increasing the efficiency of its use by reducing the cost of energy, including for the traction. It can be achieved by the way of locomotives power control systems creating, in particular the use of operating cards and on-board software and hardware. Methodo-logy. The article discusses ways of starting and acceleration of the train. Traction calculations with the definition of energy-efficient trajectories provide the search of a rational consumption of energy with time of running trains. When selecting energy saving train trajectories and the development of operating trains of reference cards, it is necessary to consider the variables such as: the profile area, weight of the stock, series of the locomotive and others. When the transmission power from the primary power equipment to the driving wheel pairs the inevitable losses that are described by the efficiency factor occur. For the most part of the locomotive elements the dependences of the efficiency factor are described by the nonlinear equations. Getting the energy-saving function of traction control at starting and acceleration to reduce the specific consumption of energy by improving the algorithm for calculating the trajectories of multiple trains was considered. The method of selection of energy-efficient trajectories at dispersal trains and power control electric and diesel locomotives with electric transmission which bases on the mathematical methods for evenly search and parametric optimization was offered. Findings. For the variables of the train situation and rolling stock was built two-parameter functional dependence of the power control locomotive and analytically determined the effectiveness of the proposed algorithm. Originality. In the work result the authors received the power saving function of traction control, which depends on the mass of the rolling stock and slant. In contrast to existing development of rational management of trains, this function requires much less computer time with a high accuracy of the calculations, which makes it possible to incorporate it into the onboard control system of the locomotive and energy savings. Practical value. Experimentally established algorithm, which is part of the on-board software package definition of energy-saving modes of conducting trains, will contribute to the reduction of energy expenses.